2014
DOI: 10.1124/jpet.114.216671
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cerebral Sigma-1 Receptor Occupancy and Attenuation of Cocaine’s Motor Stimulatory Effects in Mice by PD144418

Abstract: Psychostimulant effects of cocaine are mediated partly by agonist actions at sigma-1 (s 1 ) receptors. Selective s 1 receptor antagonists attenuate these effects and provide a potential avenue for pharmacotherapy. However, the selective and high affinity s 1 antagonist PD144418 (1,2,3,6-tetrahydro-5-[3-(4-methylphenyl)-5-isoxazolyl]-1-propylpyridine) has been reported not to inhibit cocaine-induced hyperactivity. To address this apparent paradox, we evaluated aspects of PD144418 binding in vitro, investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 31 publications
5
20
0
Order By: Relevance
“…(−)-Cocaine was selected because some behavioral effects of the drug are mediated, in part, by agonist actions at central sigma 1 and sigma 2 receptors (Matsumoto et al, 2007, 2002, 2001; Lever et al, 2014a, 2014b). (−)-Cocaine showed the same 2000 nM apparent affinity for the pulmonary sites labeled by [ 3 H](+)-pentazocine as reported for mouse brain (Matsumoto et al, 2002), and also displayed the same decided preference for binding to sigma 1 over sigma 2 receptors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(−)-Cocaine was selected because some behavioral effects of the drug are mediated, in part, by agonist actions at central sigma 1 and sigma 2 receptors (Matsumoto et al, 2007, 2002, 2001; Lever et al, 2014a, 2014b). (−)-Cocaine showed the same 2000 nM apparent affinity for the pulmonary sites labeled by [ 3 H](+)-pentazocine as reported for mouse brain (Matsumoto et al, 2002), and also displayed the same decided preference for binding to sigma 1 over sigma 2 receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Brown and colleagues (2004) suggested that dextromethorphan acts, in part, through lung sigma 1 receptors to modulate cough in a guinea pig model. We assessed dextromethorphan occupancy of sigma 1 receptors in mouse lung, spleen, heart and brain by inhibition of the uptake of [ 125 I] E -IA-DM-PE-PIPZE, a radioligand that selectively labels sigma 1 sites in vivo in mouse brain and peripheral organs (Lever et al, 2012; 2014a, 2014b). Dextromethorphan proved particularly potent in lung and heart as compared to brain and spleen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is likely that the sigma ligand ED 50 values reported herein would be right-shifted, to higher doses, during the behavioral studies conducted in the presence of methamphetamine as a competitor. We have reported that 80% occupancy of σ1 sigma receptors by very high affinity antagonist ligands is required to attenuate the locomotor stimulatory effects of cocaine by 50% (Lever et al 2014). Due to a lack of suitable radioligands, the present study did not assess in vivo binding to σ2 sigma receptors, although in vitro binding studies indicate that each ligand has less affinity for the σ2 than the σ1 receptor subtype (Lever et al 2006; Matsumoto et al 2004; Nahas et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This finding supports the notion that (−)-cocaine’s psychostimulant effects are partly due to agonist interactions with σ 1 receptors. In further support of this mode of action, [ 125 I]- E -IA-DM-PE-PIPZE was used to establish a good correlation (r 2 = 0.88) between the ability of a potent antagonist, PD144418, to occupy cerebral σ 1 receptors and to attenuate (−)-cocaine induced locomotor hyperactivity in mice [56]. Non-radioactive E -IA-DM-PE-PIPZE also partially attenuates (−)-cocaine induced locomotor hyperactivity, suggesting antagonist character [58].…”
Section: Preclinical Imagingmentioning
confidence: 99%